Konsumsi Nitrogen Dan Karbon Oleh Spirulina platensis Dari Kotoran Burung Puyuh Sebagai Media Kultivasi - Santi Amelia Putri; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2021)
The purpose of this study was to determine the level of nitrogen and carbon consumption in several variations in the concentration of quail manure as a cultivation medium for Spirulina platensis. The study was conducted from April 10 to June 19, 2020 at the Biology Laboratory of the Faculty of Science and Technology, Universitas PGRI Adi Buana, Surabaya. This study used a completely randomized design (CRD) with 4 concentrations of quail manures, each of which was repeated 5 times. The concentrations of quail manures used as the cultivation medium for S. platensis consisted of 50, 100 and 150 g/l, and Zarrouk's medium as control (0 g/l of quail manures). The results showed that the concentration of quail manures in the cultivation medium have a significant effect (P <0.05) on nitrogen and carbon consumption and S. platensis biomass. The nitrogen consumption at the quail manures concentrations of 100 and 150 g/l was significantly (P<0.05) higher than the nitrogen consumption at the concentration of 50 g/l and Zarrouk media. Carbon consumption at 150 g/l quail manures concentration was significant (P <0.05) higher than 50 and 100 g/l but significantly (P<0.05) lower than carbon consumption on Zarrouk medium. The yield of S. platensis biomass obtained from quail manure medium with a concentration of 100 g/l was significant (P<0.05) higher than 50 and 150 g/l but significantly (P<0.05) lower than the biomass obtained from Zarrouk medium. This study concluded that quail manure can be used as a source of nitrogen and carbon for S.platensis cultivation media. The concentration of 100 g/l of quail manure is the optimum concentration for use in S.platensis cultivation media. Keywords: S. platensis, quail manure, nitrogen, carbon, biomass.